Performance study on energy consumption and QoS of wireless sensor network under different MAC layer protocols: IEEE802.15.4 and IEEE802.11 - Margono F.I.; Zolkefpeli M.A.M.; Shaaya S.A. (2023)
IEEE 802.15.4 is a relatively new standard uniquely designed for low rate wireless personal area networks (LR-WPANs), which focus on low cost, efficient energy consumption and complexity. These characteristics are very appealing for wireless sensor network which mainly use IEEE 802.11 for its operation. The work would examine the performance of IEEE 802.15.4 compared to IEEE 802.11 in term of energy consumption and Quality of Services (QoS). The outcome of this work is to appraise these two MAC protocol using NS-2 simulation tool. 2009 IEEE.